Patient-reported and radiographic outcomes of minimally invasive transforaminal lumbar interbody fusion for degenerative spondylolisthesis with or without reduction: A comparative study. (November 2016) - Fan, Guoxin; Zhang, Hailong; Guan, Xiaofei; Gu, Guangfei; Wu, Xinbo; Hu, Annan; Gu, Xin; He, Shisheng
Highlights: We compared the clinical outcomes of degenerative spondylolisthesis undergoing MI-TLIF with or without reduction. MI-TLIF with reduction did not significantly improve perioperative or patient-reported outcomes, or reduce complications. Intentional reduction may not be a routine requirement in MI-TLIF for degenerative spondylolisthesis. Abstract: This retrospective study aimed to compare the patient-reported outcomes and radiographic assessment of minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) for degenerative spondylolisthesis with reduction versus in situ fusion. Patients receiving MI-TLIF with reduction were assigned as Group A, and those without reduction were assigned as Group B. Radiographic fusion was assessed using Bridwell's grading criteria. Preoperative and postoperative patient-reported outcomes including visual analogue score (VAS), Oswestry Disability Index (ODI), Japanese Orthopedic Association (JOA) scale and improvement rate were analyzed. There were 41 patients in Group A and 37 patients in Group B. The mean follow-up was 30.78 ± 14.15 months in Group A and 28.95 ± 10.75 months in Group B ( p = 0.525). There were no significant differences in hospital stay ( p = 0.261), estimated blood loss ( p = 0.639), blood transfusion ( p = 0.336), operation time ( p = 0.762) and complications ( p = 1.00) between the two groups. Radiographic fusion rate was 92.68% (38/41) in Group A, and 81.08% (30/37) in Group B ( p = 0.110). Significant differences were observed in either 3-month or last follow-up JOA, VAS, and ODI compared with preoperative JOA, VAS, and ODI, respectively ( p < 0.05). However, there were no significant differences in JOA, VAS, and ODI between the two groups whenever preoperatively, or 3-month postoperatively, or at the last follow-up ( p > 0.05). According to MacNab criteria, the excellent and good rate was 85.37% in Group A and 86.49% in Group B ( p = 0.983). MI-TLIF is an effective and satisfactory surgical technique to manage degenerative spondylolisthesis regardless of reduction or not, so routine reduction may not be a requirement in MI-TLIF for degenerative spondylolisthesis.